COMPARATIVE ANALYSIS OF PAPAIN ENZYME ACTIVITY IN DIFFERENT PARTS OF CARICA PAPAYA - T. Talabi, Olaoluwa; Oluwasanmi Anuoluwapo, Adeyemi; Moyinoluwa Talabi, Joseph; Ifunanya Divine, Okechukwu; Gisanrin, Olusola (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
Carica papaya, a neutraceutical plant known for its wide range of pharmacological activities, contains various enzymes, particularly papain, and vitamins, making it a valuable plant in the neutraceutical industry. This study aimed to investigate the enzyme activity of papain derived from unripe Carica papaya root, latex, and leaves, and determine the most effective extraction process among boiling, grinding, and latex extraction. Standard methods were employed to assess enzyme activity. The results revealed that the boiling method for leaf extraction exhibited the highest enzyme activity at a concentration of 0.1, specifically for the effect of cysteine. The stability of protease activity was observed to be highest at pH 8 (0.14 ± 0.03 nm) and pH 10, while the optimal temperature for enzyme activity was 55°C (0.11 ± 0.02 nm). At 60°C, the activity reading decreased to 0.09 ± 0.02 nm. For root enzyme activities, the optimal temperature was found to be 65°C with an activity reading of 0.10 ± 0.00 nm. Moreover, the phosphate buffer at pH 2 resulted in the optimal pH value of 0.13 ± 0.01 nm, while at pH 7, the enzyme activity reading was 0.13 ± 0.00 nm. Comparatively, the enzyme activities obtained from the latex exhibited the lowest values across different temperatures. Among the leaves, those treated with Citrate buffer at pH 3 demonstrated the highest enzyme activity of 0.16 ± 0.01 nm, whereas at pH 6, the activity reading was 0.15 ± 0.00 nm. Surprisingly, the extraction of latex showed the least value in terms of proteolytic assay of papain activity, indicating that it possessed the greatest enzymatic activity. In conclusion, this study demonstrates the diverse enzymatic activity of papain extracted from different parts of Carica papaya. It highlights the effectiveness of the boiling method for leaf extraction and provides insights into the optimal pH and temperature conditions for enzyme activity.